2022
DOI: 10.2174/0929867329666220210145033
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Curcumin in Thyroid Gland Disorders

Abstract: There is growing literature on the positive therapeutic potentials of curcumin. Curcumin or diferuloylmethane is a polyphenol obtained from the plant Curcuma longa. Curcumin has been used widely in Ayurvedic and Chinese medicine for various conditions. The role of curcumin on thyroid glands has been shown by its effects on various biological pathways, including anti-inflammatory, antioxidant, anti-proliferative, apoptosis, angiogenesis, cell cycle and metastasis. We reviewed the recent literature on curcumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…35 Curcumin has been proven to have a positive influence on thyroid gland disorders through its influence on a range of biological pathways, encompassing anti-inflammatory, antioxidant, antiproliferative, apoptosis, and angiogenesis. 11,37 However, the role of curcumin-loaded NPs as an antioxidant against T 4 -induced oxidative stress still needs to be explored. Hence, the primary objective of this study was to find out the protective activity of curcumin-loaded NPs against T 4 -induced oxidative stress like lipid peroxidation (LPx), lactate dehydrogenase (LDH) release as well as on the activity and translated products of endogenous antioxidant enzymes like SOD, catalase (CAT) and GPx in both in vitro and in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Curcumin has been proven to have a positive influence on thyroid gland disorders through its influence on a range of biological pathways, encompassing anti-inflammatory, antioxidant, antiproliferative, apoptosis, and angiogenesis. 11,37 However, the role of curcumin-loaded NPs as an antioxidant against T 4 -induced oxidative stress still needs to be explored. Hence, the primary objective of this study was to find out the protective activity of curcumin-loaded NPs against T 4 -induced oxidative stress like lipid peroxidation (LPx), lactate dehydrogenase (LDH) release as well as on the activity and translated products of endogenous antioxidant enzymes like SOD, catalase (CAT) and GPx in both in vitro and in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that nanocurcumin was more effective than curcumin in reducing hypertrophy and apoptosis, as well as downregulating atrial natriuretic factor expression, caspase‐3/‐7 activation, and oxidative stress 35 . Curcumin has been proven to have a positive influence on thyroid gland disorders through its influence on a range of biological pathways, encompassing anti‐inflammatory, antioxidant, antiproliferative, apoptosis, and angiogenesis 11,37 . However, the role of curcumin‐loaded NPs as an antioxidant against T 4 ‐induced oxidative stress still needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous preclinical and clinical investigations have solidified the therapeutic promise of Cur by offering detailed mechanistic insights into various conditions linked to endocrine disorders. These encompass DM, thyroid disorders, primary adrenal insufficiency, pituitary tumors, as well as hormonal imbalances related to the reproductive system and cancer (Klinger & Mittal, 2016; Patel et al, 2020; Pivari et al, 2019; Shakeri et al, 2022; Woźniak et al, 2021). Several studies have provided a comprehensive understanding of the molecular mechanisms through which Cur and other extracts from plants contribute to the pathologies associated with endocrine disorders (Bulotta et al, 2021; Kamal et al, 2021; Marton et al, 2021; Shrivastava, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have provided a comprehensive understanding of the molecular mechanisms through which Cur and other extracts from plants contribute to the pathologies associated with endocrine disorders (Bulotta et al, 2021; Kamal et al, 2021; Marton et al, 2021; Shrivastava, 2022). However, there exists a notable absence of a comprehensive and comparative documentation of the therapeutic effects of Cur in endocrine disorders related to hormones (Kamal et al, 2021; Shakeri et al, 2022). To fill this gap, this review aims to present an integrated perspective on the advantageous impact of Cur in the context of dysfunctions associated with endocrine hormones.…”
Section: Introductionmentioning
confidence: 99%
“…A turmeric polyphenol generated from Curcuma longa , curcumin is an orange–yellow substance that is a member of the Zingiberaceae family (Bavarsad et al, 2019). Curcumin has a wide range of pharmacological effects, including antiinflammatory, antioxidant, antibacterial, and anticarcinogenic qualities (Afshari et al, 2021; Akar et al, 2017; Farhood et al, 2019; Gorabi et al, 2019; Heidari, Daei, Boozari, Jamialahmadi, & Sahebkar, 2022; Iranshahi et al, 2009; Mohammed et al., 2020; Mohammed et al, 2021; Panahi et al, 2017; Parsamanesh, Moossavi, Bahrami, Butler, & Sahebkar, 2018; Shakeri, Cicero, Panahi, Mohajeri, & Sahebkar, 2019; Shakeri et al, 2022). Curcumin has also been shown +++ play a protective effect in a variety of experimental IR injury models, including those for cardiac, renal, hepatic, and brain damage.…”
Section: Introduction To Ischemia–reperfusion Injurymentioning
confidence: 99%